Cultural Heritage and the Attractiveness of Cities: Evidence from Recreation Trips - Ruben van Loon; Tom Gosens; Jan Rouwendal (Tinbergen Institute, 2014)
Many cities are trying to attract tourists by investing in urban amenities. Cultural heritage is an important example and substantial investments are needed to keep ancient inner cities and characteristic monumental buildings in good shape. The costs of these policies are usually clear, the benefits are often much more difficult to assess. This paper attempts to fill part of this gap by studying the destination choices of urban recreation trips that have urban recreation as the main travel motive. We estimate a discrete choice model for destination choice that takes into account the potential importance of unobserved characteristics. The model allows us to compute the marginal willingness to travel for destinations offering more cultural heritage, which we measure as the area of the inner city that has a protected status because of the cultural heritage that is present there.
Keywords: C31; D12; R12; R22; L83; 330; Cultural heritage; recreation; city marketing